The impact of rotavirus vaccination on acute diarrhea in Thai children under 5 years of age in the first year of universal implementation of rotavirus vaccines in the National Immunization Program (NIP) in Thailand: a 6-year analysis - Busara Charoenwat; Kunanya Suwannaying; Watuhatai Paibool; Napat Laoaroon; Sumitr Sutra; Kaewjai Thepsuthammarat; Suphasarang Sirirattanakul (BMC, 2023)
Abstract Background Two types of rotavirus vaccines (RVs), Rotarix (RV1) and RotaTeq (RV5), were licensed as optional vaccines in 2012 and became part of the National Immunization Program (NIP) in the fiscal year 2020 in Thailand. The main objective was to evaluate the impact of rotavirus vaccines on the burden of acute diarrheal severity ranging from outpatient visits, diarrheal-related admission or deaths in the pre-NIP period (fiscal year 2015-2019) and in the fiscal year 2020. The minor objectives were assessed on the monthly admission rate, rotavirus vaccine coverage rate and rotavirus vaccine completed dose (RotaC). Methods Data regarding OPD, admission, and death cases under the Thailand National Health Coverage (NHC) from fiscal year 2015-2020, which were recorded as International Classification of Diseases and Related Health Problem 10th (ICD-10), were analyzed. Results The burden of diarrheal-related disease diminished after the rotavirus vaccine was introduced in the fiscal year 2020 when compared to the previous 5 fiscal years. The OPD visit rate decreased from 10.1 to 8.3 visits per 100 person-years (P < 0.001), or a 17.8% reduction (incidence rate ratio (IRR) = 0.82; 95% confidence interval (CI): 0.81 to 0.82). The admission rate significantly declined from 31.4 to 30.5 cases per 1,000 person-years, (P < 0.001), or a 2.9% reduction (IRR = 0.97; 95% CI: 0.96 to 0.98). The diarrheal-related mortality rate also subsided from 10.2 to 8.1 cases per 100,000 person-years (P 0.3), or a 20.0% reduction (IRR = 0.88; 95% CI: 0.50 to 1.22). The major population in both admissions and deaths was infants under 1 year of age (P < 0.001). Seasonality was seen as a constant bimodal pattern, with a significant decrease in monthly admissions after 6 months of rotavirus vaccine introduction to NIP (P < 0.001). RotaC was 37.4% in the first year of NIP. Conclusions The rotavirus vaccine had a potential benefit for reducing the diarrheal disease burden, especially in infants under one year of age. Seasonality outbreaks of acute diarrhea subsided after the rotavirus vaccine was introduced. The RotaC was fairly low in the first year of the NIP. The quality of the rotavirus vaccine should be warranted. Trial registration Number TCTR20220120003 , date of registration: 20/01/2022, site: Thai Clinical Trials Registry.